Perancangan Sistem Informasi Pelayanan Akademik Berbasis Recommender System - Muhamad Faza Almaliki; Musaruddin, Mustarum; Tari Mokui, Hasmina (Jurnal Informatika, 2024)
This study aims to develop an academic service information system based on a recommender system in the Department of Computer Engineering at UHO to address challenges in managing academic documents and enhancing user satisfaction. The methods employed include needs analysis, web-based system prototype development, and evaluation using Black Box Testing to ensure system functionality. The implementation of the User-Based Collaborative Filtering (UBCF) algorithm enables the system to provide personalized recommendations to students, assisting them in accessing relevant information while reducing the administrative burden on academic staff. The results of this study indicate that the system is effective in improving academic service efficiency and can serve as a reference for developing similar services in other educational institutions